Microbial mismanagement: how inadequate treatments for vaginal dysbiosis drive the HIV epidemic in women. (January 2021) - Gustin, Andrew; Cromarty, Ross; Schifanella, Luca; Klatt, Nichole R.
Abstract: Women and girls represent a key population driving new HIV infections and persistence of the HIV pandemic. A key determinant of HIV susceptibility is the composition of the vaginal microbiome, which can influence the local immune cell population, inflammation status, and HIV prevention drug levels. While a low-diversity composition dominated by Lactobacillus crispatus is associated with a decreased risk of HIV acquisition, high diversity environments associated with bacterial vaginosis increase risk of HIV. Given the important role of the vaginal microbiome in determining HIV susceptibility, altering the microbiome towards a Lactobacillus -dominated state is an attractive complementary strategy to reduce HIV incidence rates. Here, we provide an overview of the mechanisms by which the vaginal microbiome may contribute to HIV acquisition risk. Furthermore, we address the advantages and limitations of historical treatments and emerging technologies under investigation to modify the vaginal microbiome, including: antibiotics, bacteriophages, probiotics, topicals, and engineered bacteria. By addressing the current state of vaginal microbiome knowledge and strategies for manipulation, we hope to amplify the growing calls for increased resources and research into vaginal microbial health, which will be essential to accelerating preventative efforts amongst the world's most vulnerable populations.